Predictive Quality Orchestration as a Tool for Minimizing Operational Losses in Globally Distributed Development - Kharchenko, Iryna (Актуальні питання економічних наук, 2026)
The increasing complexity of software systems, the proliferation of globally distributed teams, and the intensification of release cycles necessitate the development of approaches to reduce operational losses in software development processes. Traditional quality assurance models fail to adequately account for the multifactorial nature of risks arising in CI/CD environments, which limits the ability to make timely and well-informed managerial decisions. The aim of this study is the formalization of an approach to predictive quality orchestration as a tool for minimizing operational losses through the integration of a multifactor risk assessment model, indicator normalization, and automation of release decisions. The methodological framework of the study is based on methods of systems analysis, economic and mathematical modeling, data normalization, threshold analysis, and simulation modeling. The study employs an integrated quality risk score (QRS) that combines key development process parameters, including code complexity, defect density, change volatility, test coverage, and interaction stability. To validate the approach, a simulated sample of software modules was constructed, followed by the calculation of normalized values and the integrated risk score. The results demonstrate the feasibility of differentiating software modules by release readiness level and establishing a direct relationship between technical parameters and potential operational losses. The proposed model enables a reduction in the proportion of failed releases, a decrease in rollback operations, mitigation of deployment delays, and a reduction in post-release defects. The formalization of decision-making based on the QRS enhances coordination across distributed teams and facilitates a transition to proactive risk management. The conclusions substantiate the complex nature of operational losses in globally distributed software development and confirm the effectiveness of the proposed approach to predictive quality orchestration based on the integrated QRS indicator.